Synergize in Empowering Students to Serve Change in Jaranguda Village in Karo District - Hadi, Firman Hadi; Salsabina, Laila; Aidin, Winda; Tuffahati, Jihan; Husnah, Malika Aulia; Lubis, Nurul Mupida; Marpaung, Syafri Fadillah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This abstract discusses the importance of synergy in empowering students to serve for change. Synergy here refers to close collaboration between various parties, such as universities, governments, and communities, to create an environment that supports and facilitates the role of students in community service. This article will examine how these synergies can increase the impact of student service, encourage social innovation, and create positive change in various fields. It is hoped that this abstract can provide an initial overview of the importance of synergy in empowering students to serve for change and encourage further research in this field.